Building Discretionary Authority in a Teacher Education Program. (2nd April 2016) - Baker, Scott; Milner, Joseph O.
ABSTRACT: This article reports on a teacher education program's use of teaching rounds and action research to build teacher candidates' discretionary authority, the confidence to make their own teaching decisions rather than model their classroom choices solely on a mentor teacher's classroom pedagogy. Discretionary authority is promoted by many contemporary business and government organizations as a central feature of the transformational leadership that Burns long ago contrasted with transactional leadership. The impact of candidates' discretionary authority is validated by the top marks awarded by their principals and mentors on the NC Department of Public Instructions IHE Performance Report. Their independence of mind is further corroborated by the important accomplishments they achieved in their first 5 years of teaching.